Inapproximability and Polynomial-Time Approximation Algorithm for UET Tasks on Structured Processor Networks - Bouznif, M.; Giroudeau, R. (Advances in Operations Research, 2011)
We investigate complexity and approximation results on a processor networks where the communication delay depends on the distance between the processors performing tasks. We then prove that there is no heuristic with a performance guarantee smaller than 4/3 for makespan minimization for precedence graph on a large class of processor networks like hypercube, grid, torus, and so forth, with a fixed diameter δ∈ℕ. We extend complexity results when the precedence graph is a bipartite graph. We also design an efficient polynomial-time O(δ2)-approximation algorithm for the makespan minimization on processor networks with diameter δ.Erratum to “Inapproximability and Polynomial-Time Approximation Algorithm for UET Tasks on Structured Processor Networks”dx.doi.org/10.1155/2012/543215